(The effect of Concentration of Pepper Oleorecin Solution On Rice Quality During Storage) - Sugesti, Karyati; Antara, Ngakan Timur; Djanaka, R; -, Soim (Balai Besar Industri Agro, 1987)
Â A study on the effect of oleoresin on rice quality during storage has been coducted. Four treatment were done i.e. spraying using pepper oleoresin of 200, 250, 300 ppm and control. Each treatment used 5 kgs rice packed in gunny sacks. Spraying were done on the sacks. Observation on the amounth of rice weevil, texture, taste, flavor and colour, was done every two months. The result showed that up to four months storage, the amounth of weevil in rice sprayed with 250 ppm oleoresin decreased by 70.74% as compared to control, and have the most preffered texture and colour, more preffered flavor as compared to control and no significantly different taste as compared to other treatments. Up to six months storage, the same treatment decreased the amounth of weevil by 49.76%, while those with higher concentration (300 ppm) decreased the weevil by 66.08% but the texture, taste and colour were not significantly different as compared to other treatments.